Інтеграція принципів ESG у бізнес-модель підприємств роздрібної торгівлі: вплив на управління ризиками та економічну безпеку - Коптєва, Г.М. (Економічний вісник Донбасу, 2026)
У статті досліджено роль інтеграції принципів ESG у бізнес-модель підприємств роздрібної торгівлі як сучасного інструменту управління ризиками та зміцнення економічної безпеки підприємства. Обґрунтовано механізм опосередкованого впливу ESG-інтеграції на її рівень через трансформацію управлінських рішень, бізнес-процесів і взаємодії зі стейкхолдерами. Запропоновано узагальнену логіку впливу інтеграції принципів ESG у бізнес-модель підприємств роздрібної торгівлі, яка формалізує взаємозв’язок між елементами бізнес-моделі, групами ризиків і відповідними складовими економічної безпеки. The article examines the role of integrating Environmental, Social, and Governance (ESG) principles into the business model of retail enterprises as a contemporary tool for risk management and strengthening enterprise economic security. The content of the retail enterprise business model is specified as a systemic configuration of the value proposition and the logic of commercial activity, encompassing the full commodity circulation cycle from procurement to final sale and acting as an object of purposeful transformation under the influence of ESG principles. The expediency of considering ESG not as a separate direction of corporate policy, but as a cross-cutting element of the business model that affects the risk structure and the level of protection of the enterprise’s economic interests, is substantiated. The mechanism of the indirect impact of ESG integration on the level of economic security is justified through the transformation of managerial decisions, business processes, and stakeholder interactions. It is demonstrated that the environmental component of ESG contributes to the reduction of resource-related, logistics, and financial risks, the social component reduces human resource, market, and reputational risks, while the governance component mitigates managerial, financial, and compliance-related risks. This ensures a qualitative transformation of the risk structure of retail enterprises and contributes to the enhancement of their economic security. A generalized logic of the impact of ESG integration into the business model of retail enterprises is proposed, which formalizes the interrelationship between business model elements, groups of risks, and the corresponding components of economic security. The practical significance of the obtained results lies in the possibility of applying the proposed approaches to the development of ESG-oriented managerial decisions aimed at risk reduction and increasing the resilience of the economic activity of retail enterprises.